2020
DOI: 10.3389/fpsyt.2020.00520
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Correlates of Poor Sleep Quality Among Frontline Health Professionals in Liaoning Province, China During the COVID-19 Outbreak

Abstract: Background: Little empirical evidence is known about the sleep quality of frontline health professionals working in isolation units or hospitals during the novel coronavirus disease (COVID-19) outbreak in China. This study thus aimed to examine the prevalence of poor sleep quality and its demographic and correlates among frontline health professionals.Methods: This is a multicenter, cross-sectional survey conducted in Liaoning province, China. Sleep quality was measured by the Pittsburgh Sleep Quality Index (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 39 publications
9
96
3
1
Order By: Relevance
“…The prevalence rate of sleep disturbance in 18 studies [ 24 , 26 , 36 , 48 , 52 , 55 , 56 , 59 , 72 , 79 , 82 , 84 , 86 , 88 , 96 , 104 , 109 , 110 ] ranged from 12% to 87% ( Fig. 5 : Forest plots) with pooled prevalence estimates of 43% (4082/10,697 participants, 95% CI 36–50).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rate of sleep disturbance in 18 studies [ 24 , 26 , 36 , 48 , 52 , 55 , 56 , 59 , 72 , 79 , 82 , 84 , 86 , 88 , 96 , 104 , 109 , 110 ] ranged from 12% to 87% ( Fig. 5 : Forest plots) with pooled prevalence estimates of 43% (4082/10,697 participants, 95% CI 36–50).…”
Section: Resultsmentioning
confidence: 99%
“… China Cross –sectional media platform-based smartphone Children’s Healthcare Centre of Renmin Hospital of Wuhan 123 33.75(8.41) 90 75 48 PSQI > 7 24 60.4 5 Zhang, C. X.2020 [ 16 ]. China Cross sectional questionnaire delivered through the mobile phone, WeChat hospital staff from all over China, including the frontline medical workers in Wuhan 1563 > 18 82.7 984 454 ISI > 8 40.1 27.3 6 Tu, Zhi-hao.2020 [ 28 ] China Cross sectional questionnaire delivered through the mobile phone, WeChat “Huoshenshan” Hospital in Wuhan 100 34.44(5.85) 100 100 _ PSQI > 7 60 _ 7 Zhou, Y.2020 [ 29 ]. China Cross –sectional using the Wenjuanxing program which is an application embedded with WeChat, hospital in Liaoning province, China 1931 35.08(8.04) 12 1614 _ PSQI > 7 19.5 _ …”
Section: Resultsmentioning
confidence: 99%
“…According to our study, the prevalence of sleep disturbances among nurses is 34.8% (95% CI: 24.8-46.4%). The lowest prevalence reported in the research conducted by Zhou et al (2020) and was reported as 19.5% (95% CI: 17.6-21.54%) [ 29 ]. Tu et al (2020) reported the highest prevalence of sleep disturbances among nurses with 60% (95% CI: 50.1-69.1%) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontline nursing and medical staff, especially in the early stages of epidemics, have suffered from anxiety and depression due to high workload, insufficient personal protective equipment, lack of knowledge of the pathogen and direct contact with patients (7)(8)(9)(10). Consequently, nurses have commonly reported to experience a greater decline of morale and decreased job satisfaction due to the nature of the profession (11).…”
Section: Introductionmentioning
confidence: 99%